COMPARATIVE ANALYSIS OF FRICTION MASSAGE AND CONTRAST BATH VERSUS STRETCHING EXERCISE AND CONTRAST BATH IN PATIENTS WITH PLANTAR HEEL PAIN - VINITHA P; SAI SURYA PRAKASH (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The main objective of this study is to analyze the synergistic effect of friction massage and stretching exercise with contrast bath in a patient with plantar heel pain. Methods: The procedure to perform friction massage and stretching exercises was performed among 30 patients each separately. Further, all were subjected to a contrast bath for a maximum of 20 min thereby 3 min for warm and 1 min for cold and this procedure was repeated 5 times. Results: As a result, comparing with friction massage and contrast bath, stretching exercise and contrast bath were effective and the patients felt reduced pain while following the course completely. Conclusion: By this effective therapeutic intervention, the patients felt satisfaction in reducing pain thereby their activities of daily living improved with self-management.